PENGEMBANGAN BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN MINAT BACA SISWA KELAS IV SEKOLAH DASAR - Nova Triana Tarigan (Universitas Quality, 2019)
The purpose of this paper is to know the effectiveness of picture storybook to improve student's interest in reading of the fourth-grade students of an elementary school in Yogyakarta. The Enhancement of student’s interest in reading of elementary school need to be surmounted with the right media in process learning. It aims to improve student's interest in reading through picture storybook effectively. The paper used quasi-experiment. The technique of analysis data to know the effectiveness picture storybook used pairs sample t-test with improved significant 0.05. The result of this paper shows that the learning process with picture storybook effective improves student's interest in reading with score -26,317 with the probability (sig) 0.000. This paper suggests that interest in reading can improve by picture storybook. The elements of picture storybook can improve student's interest in reading.